The Role of Artificial Intelligence in Dental Diagnosis (International Journal of Scientific Research and Management (IJSRM), 2024)
This paper discusses the potential role of artificial intelligence in enhancing dental diagnosis and care delivery. It describes how AI shows promise in automatic detection of abnormalities in dental images, personalised disease risk assessment through predictive modelling, and generation of comprehensive examination reports. The ability of AI to analyse patterns across medical imaging, genetics, lifestyle factors and health records enables more holistic understanding of oral health in relation to systemic conditions. Clinical decision support through differential diagnoses and evidence-based treatment recommendations aims to augment dentists’ decision making. Seamless integration of AI into clinical workflows through interfaces is emphasised as important for adoption. Challenges around data and model validation are also addressed. Continued development of AI aims to realise benefits like earlier disease identification and more proactive, personalised care approaches